Cohort profile of a study on outcomes related to tuberculosis and antiretroviral drug concentrations in Uganda: design, methods and patient characteristics of the SOUTH study. Issue 9 (18th September 2017) - Sekaggya-Wiltshire, Christine; Castelnuovo, Barbara; von Braun, Amrei; Musaazi, Joseph; Muller, Daniel; Buzibye, Allan; Gutteck, Ursula; Henning, Lars; Ledergerber, Bruno; Corti, Natascia; Lamorde, Mohammed; Fehr, Jan; et al.
Abstract : Purpose: Tuberculosis (TB) is a leading cause of death among people living with HIV in sub-Saharan Africa. Several factors influence the efficacy of TB treatment by leading to suboptimal drug concentrations and subsequently affecting treatment outcome. The aim of this cohort is to determine the association between anti-TB drug concentrations and TB treatment outcomes. Participants: Patients diagnosed with new pulmonary TB at the integrated TB-HIV outpatient clinic in Kampala, Uganda, were enrolled into the study and started on first-line anti-TB treatment. Findings to date: Between April 2013 and April 2015, the cohort enrolled 268 patients coinfected with TB/HIV ; 57.8% are male with a median age of 34 years (IQR 29–40). The median time between the diagnosis of HIV and the diagnosis of TB is 2 months (IQR 0–22.5). The majority of the patients are antiretroviral therapy naive (75.4%). Our population is severely immunosuppressed with a median CD4 cell count at enrolment of 163 cells/µL (IQR 46–298). Ninety-nine per cent of the patients had a diagnosis of pulmonary TB confirmed by sputum microscopy, Xpert/RIF or culture and 203 (75.7%) have completed TB treatment with 5099 aliquots of blood collected for pharmacokinetic analysis. Future plans: This cohort provides a large database of well-characterised patients coinfected with TB/HIV which will facilitate the description of the association between serum drug concentrations and TB treatment outcomes as well as provide a research platform for future substudies including evaluation of virological outcomes. Trial registration number: NCT01782950; Pre-results.